Fetal Outcome in Pregnancy with Oligohydramnios - Aneela, Asma Unar, Zakia Zaheen, Maria, Shazia Ahmed Jatoi, Fozia Irum, Kiran Aamir, Aasma Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to calculate the frequency of adverse fetal outcomes in oligohydramnios pregnancies. Study Design: Descriptive study Place and Duration: Department of Obstretics and Gynaecology,PUMHS Nawabshah Hospital. August 2018-February 2019 Methods: A total of 164 pregnant women with oligohydromnios were included in this study. Diagnosis was established after detailed history and abdominal examination. An extensive obstetric ultrasound was performed to verify the presence of alcohol, the baby's viability, the presence of two congenital defects, and the presence of the fetal heartbeat using Doppler ultrasonography. Information will then be filled in the performa. SPSS 22.0 was used to analyze all data. Results: The average age of the women was 25.76±4.18 years. Out of 164 cases, fetal growth retardation was observed in 39.02%, low birth weight 34.15%, NICU admission 30.5%, birth axpysia 27.44%, respiratory distress syndrome 12.8%, Apgar scores <7 at1 minutes 43.35% and at 5 minutes 23.2%, meconium aspiration syndrome 4.27% and perinatal mortality was observed in 4% . Conclusion: Assessment of AFI in the first part of the third trimester helps to identify women who need greater antepartum surveillance, and hence, correct care, to enhance perinatal outcome. Keywords: Oligohydramnios, Birth axpysia, Low birth weight